Early Life Factors Predictive of Weight Status in 2 Year-Olds. (29th May 2020) - Dinsmoor, Andrew; Arthur, Anna; Fiese, Barbara; Khan, Naiman; Donovan, Sharon
Abstract: Objectives: The extent to which early life factors predict weight status by age two is unclear. This study elucidated early life factors predictive of BMI-for-age z-score (MN24 BMI) in 2-year-olds in the ongoing STRONG Kids 2 longitudinal study. Methods: At registration, 6 weeks, 3, 12, 18, and 24 months, parents (N = 126) completed online surveys (questions derived from CDC Infant Feeding Practices questionnaire, Short Form of the MOS Health survey, and Block Kids Food Frequency Questionnaire (Ages 2–7; Nutrition Quest) for diet MN21–24). Height and weight were collected at home visits. Child BMI-for age z-scores were based on WHO growth standards, and dietary patterns at MN24 were derived by principal component analysis (PCA). Mode of delivery (i.e., vaginal or caesarean), timing of introduction to solids, dietary patterns, child's BMI z-score and feeding methods (i.e., exclusive formula or breastfeeding, or both), and maternal weight were obtained. Multiple regression modelling determined the explanatory power of these factors on MN24 BMI. Results: Modelling revealed a significant regression equation ( P  < .001), with an R2 of .359. MN12 BMI-for-age z-score (MN12 BMI) (β = .555, P  < .001) explained 31.2% of the variance in MN24 BMI. Child feeding method at MN3 (β = –.218, P  = .003) accounted for 4.7% of the variance in MN24 BMI. Conclusions: Children with a greater MN12 BMI have a higher MN24 BMI, while those who undergo breastfeeding at MN3 have a lower MN24 BMI. Future studies will expand on these findings by examining if the predictive power of these early life factors on BMI persists in later life. Funding Sources: Grants from the National Dairy Council to Sharon Donovan and Barbara H. Fiese (CoPI's), and the Gerber Foundation and NIH R01 DK107561 to Sharon Donovan.